Field-based assessment of rock discontinuity and geological attributes of rock mass for stones for various engineering applications (Journal of Nepal Geological Society, 2018)
Because of the occurrence of various rock types within the short span of areas, the Malekhu Khola area is one of the most promising areas where scope of stones is high. This paper presents recognition of the most promising rock types in terms of their geology and discontinuity for evaluating suitability for building stones. The research focuses on the assessment of nine different rock types allocated along the Malekhu Khola, central Nepal. Geological parameters, rock mass characterization and discontinuity analysis were carried out in each of allocated sites. During field study, rock masses were categorised based on different geological parameters, and on number of joint set, tentative block shape, size and volume. Field-based data were tabulated, analysed, and finally identified for the block size and geometry, and rock mass quality for stones. The number of major joint set ranges from one to four with random joint sets. The study shows that the outcrop condition of rock is faintly to slightly weathered and strongly indurated. The study shows that the rock types depending on the Rock Mass Rating (RMR) system vary from poor to very good. The block types that could be extracted are flat, long and compact. The probable end uses of these rock types could be armourstone, interior and exterior paving, cladding and foundation.